Pengaruh Sustainability Report, Vitalitas, Intellectual Capital terhadap Nilai Perusahaan (Effect of Sustainability Report, Vitality, Intellectual Capital on Firm Value) - Tjandra, Ivena; Lindrawati, Lindrawati; Susanto, Adi; Lindrawati Lindrawati (Akutansi Bisnis & Manajemen ( ABM ), 2023)
The purpose of this study is to examine and analyze the factors that affect the value of banking companies. The type of data used is quantitative data in the form of company annual reports and sustainability reports. The object of research is banking companies listed on the Indonesia Stock Exchange in 2017-2019. Data were analyzed using multiple linear regression whose results showed disclosure of sustainability reports and intellectual capital had no effect on firm value. In addition, the level of bank vitality in the form of earnings has a positive effect on firm value, while the risk profile, good corporate governance, and capital have no effect on firm value.